Effect of drying methods on the thermodynamic properties of blackberry pulp powder (2011)
Three different types of maltodextrin encapsulated dehydrated blackberry fruit powders were obtained using vibrofluidized bed drying (VF), spray drying (SD), vacuum drying (VD), and freeze drying (FD). Moisture equilibrium data of blackberry pulp powders with 18% maltodextrin were determined at 20, 30, 40, and 50°C using the static gravimetric method for the water activity range of 0.06–0.90. Experimental equilibrium moisture content data versus water activity were fit to the Guggenheim–Anderson–de Boer (GAB) model. Agreement was found between experimental and calculated values. The isosteric heat of sorption of water was determined using the Clausius–Clapeyron equation from the equilibrium data; isosteric heats of sorption were found to increase with increasing temperature and could be adjusted by an exponential relationship. For freeze dried, vibrofluidized, and vacuum dried pulp powder samples, the isosteric heats of sorption were lower (more negative) than those calculated for spray dried samples. The enthalpy-entropy compensation theory was applied to sorption isotherms and plots of ΔH versus ΔS provided the isokinetic temperatures, indicating an enthalpy-controlled sorption process.